Ca-ALGINAT UNTUK ADSORPSI Fe DAN Mn PADA AIR GAMBUT - Elliska Murni Harfinda (JURNAL KIMIA MULAWARMAN, 2020)
Ca-alginate for the adsorption of Fe and Mn in peat water has been carried out using a batch method. Brownish water color, low pH, and high content of Fe and Mn metals are obstacles in direct utilization of peat water. Peat water treatment can be done by the adsorption method. The stages of this study began with the preparation of the adsorbent by dripping Na-alginate solution into a variety of CaCl2 solution concentrations. Furthermore, the adsorption of peat water was carried out by batch method with variations in the contact time and mass of the adsorbent to get the adsorbent with the highest % removal. The optimal contact time for Fe and Mn adsorption on peat water is 6 hours. The optimal % removal value for the influence of Fe adsorption contact time for Ca-alginate variations of 0.1 M and 0.2 M CaCl2 solution were 20.38% and 21.19%, respectively. The optimal % removal value for the influence of Mn adsorption contact time for Ca-alginate variations of 0.1 M and 0.2 M CaCl2 solution were 30.98% and 41.37%, respectively. The optimal mass of adsorbent for Fe and Mn adsorption in peat water is 0.75 g. The optimal % removal value for the influence of Fe adsorption mass adsorption for Ca-alginate variations of 0.1 M and 0.2 M CaCl2 solution were 79.28% and 21.67%, respectively. The optimal % removal value for the mass effect of Mn adsorption adsorption for Ca-alginate variation of 0.1 M and 0.2 M CaCl2 solution respectively at 24.44% and 26.13%.